Polarimetric RCS Calibration using Reference Reflectors - Lo, Y. C.; Chung, B. K. (2005)
A new polarimetric radar cross section (RCS) calibration technique using two reference reflectors is developed and verified experimentally in the anechoic chamber of Multimedia University. The antenna system and the two orthogonal channels are modeled as a two-port network. The technique utilizes two electrically large reflectors, namely a rectangular flat plate and a 45 degrees rotated dihedral corner reflector as the calibration targets to provide large reflections for co-polarization and cross-polarization returns, respectively. The orientation of the reflectors is not critical, and their theoretical RCS are not required in the calibration process. Therefore the alignment problem and uncertainties in the computation of the theoretical responses are eliminated. A metallic sphere with known theoretical RCS is used to verify the calibration accuracy and determine the correction factor for absolute RCS measurement. Scattering measurements are performed using a Vector Network Analyzer (VNA). Raw data are acquired and stored in the PC for further processing. Time domain gating technique is applied to remove the target-chamber coupling effect in the measurements.